Tectonic evolution of the Circum-Moesian orocline of the Carpatho-Balkanides: Paleomagnetic constraints - Márton, Emő; Cvetkov, Vesna; Banješević, Miodrag; Imre, Gábor; Pačevski, Aleksandar (Journal of geodynamics, 2024)
The areas of the present study in eastern Serbia, the Danubicum and the Timok Magmatic Complex (TMC, part of the Geticum) are situated between the Vardar Zone and Moesia. The first is Moesia derived and thrust over the Geticum during the latest Cretaceous, the second represents the central segment of the subduction related Apuseni-Banat-Timok-Srednogorie (ABTS) metallogenic belt. The new results, based on 18 geographically distributed sampling points (228 field oriented drill cores) imply large CW vertical axis rotations for the Upper Jurassic (Lower Cretaceous) carbonates of the Danubicum and a moderate one for the Upper Cretaceous igneous and sedimentary rocks from the TMC. These, together with earlier published paleomagnetic data provide kinematic constraints to test the circum-Moesian backarc-convex orocline model. The strike test plot clearly documents that it is a progressive arc. The starting situation at the time of the volcanic activity in the metallic belt (90–70 Ma) must have been a generally E-W oriented S segment, continuing in NNW-SSE oriented ABT segments. The present geometry of the circum-Moesian belt, in the context of Miocene paleomagnetic results from the Vardar Zone and the Apuseni Mts, is interpreted as the result of two main tectonic processes. The first is an about 30° vertical axis CW rotation which took place in coordination with the Vardar Zone (20–17 Ma). The second is an additional 40–65° CW rotation (17–15 Ma) involving also the Danubicum, due to the subduction pull of the E Carpathians in combination with the corner effect of Moesia. •New paleomagnetic results document post-Cretaceous CW rotations for Eastern Serbia.•Those from the Timok area provide a new piece of constraints for the ABTS belt.•Strike test plot documents that the Moesian orocline is a progressive arc.•The NNW-SSE oriented Late Cretaceous ABT segments rotated twice between 20 and 15 Ma.•Rotation with the Vardar Zone (20–17 Ma) was followed by a larger one around Moesia.